Pengaruh Media Virtual Reality Berbasis STEAM Terhadap Literasi SAINS pada Pembelajaran IPA di Sekolah Dasar - Fadhli Omi Raharjo; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
The purpose of this research is to determine the influence of STEAM-based virtual reality media on Science Literacy in Science Education at the Elementary School level, specifically in terms of content, context, competence, and attitude. The research design used is a Quasi-Experimental or quasi-experimental study with a Pretest-Posttest Control Group design to examine the impact of using virtual reality media with a STEAM approach on content, context, competence, and science literacy attitude. Based on the research findings, it can be concluded that STEAM-based virtual reality media is suitable for use as teaching material in the 6th-grade Science curriculum, specifically on the topic of the solar system. The validation results show a percentage of 80% for content, 78% for language, and 86% for design. The research results indicate that in terms of content, the average learning outcomes of the experimental group were 38.04, while the control group had an average of 20.23, as evidenced by the Mann-Whitney test for science literacy. In terms of context, the average learning outcomes of the experimental group were 36.69, compared to 21.40 for the control group. Regarding competence, the inferential test for science literacy showed a mean rank of 39.79 for the experimental group and 18.73 for the control group. As for attitude, the inferential test results revealed a mean rank of 89.13 for the experimental group and 82.67 for the control group. Thus, it can be concluded that there is an influence of STEAM-based virtual reality media on the content, context, competence, and attitude aspects of Science Literacy in Science Education at the elementary school level.